2020
DOI: 10.23960/ja.v19i2.4544
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Formulasi Biochar Dan Limbah Kulit Kopi Terhadap Pertumbuhan Bibit Kopi

Abstract: Coffee husk is the main waste of coffee bean production using a dry processing system. Coffee husk is returned to the coffee plantation as mulch, or used as a mixture for nursery media and for making bio-charcoal. This study aims to determine the effect of the formulation of biochar, coffee husk, and soil on the growth of Arabica coffee seedlings. The experiment used a randomized block design (RBD) consisting of 6 treatments with 4 replications. The treatments were the composition of the ratio of biochar: coff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Meanwhile, a preliminary study showed that the media concentration of 1/8 MS had the best effect on the number of pitchers, number of roots, percentage of live plantlets, percentage of plantlet's pitchers, and percentage of rooted plantlets in N. rafflesiana [26]. Another report on research results on the formation of pitchers in N. mirabilis and N. ampullaria, which are better on ¼ MS and ½ MS media [24]. Another study showed that the highest number of pitchers was found when N. ampullaria was cultured on an MS media without nitrogen [27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, a preliminary study showed that the media concentration of 1/8 MS had the best effect on the number of pitchers, number of roots, percentage of live plantlets, percentage of plantlet's pitchers, and percentage of rooted plantlets in N. rafflesiana [26]. Another report on research results on the formation of pitchers in N. mirabilis and N. ampullaria, which are better on ¼ MS and ½ MS media [24]. Another study showed that the highest number of pitchers was found when N. ampullaria was cultured on an MS media without nitrogen [27].…”
Section: Resultsmentioning
confidence: 99%
“…The more deficient the nutrient content of the media, the more and larger the pitchers are likely to form [6]. Large pitchers formed on nutrient-poor media (1/16 MS) compared to the other nutrient-rich media [6,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengan bahan baku sekam padi, temperatur pirolisis yang rendah (300 o C) memberikan hasil karbon yang rendah (49-70%) sedangkan pada temperatur tinggi (600 o C) memberikan hasil karbon mencapai 85-93% (Oni et al 2019). Pembakaran pembuatan biochar metode tungku bercerobong dari bahan kulit kopi membutuhkan waktu 1 hari (Hanisah et al 2020). Pembakaran untuk pembuatan arang secara tradisional menggunakan metode soil pit membutuhkan waktu 5-6 hari (Iskandar and Santoso 2005).…”
Section: Kandungan Biocharunclassified